2018
DOI: 10.37914/riis.v1i2.38
|View full text |Cite
|
Sign up to set email alerts
|

Cuidaoaz: Satisfação dos Cuidadores Familiares de Idosos Dependentes em Oliveira de Azeméis

Abstract: Enquadramento: o envelhecimento da população aumenta a probabilidade de conduzir os idosos a situações de dependência no autocuidado. Perante esta nova condição, a família surge como um recurso, constituindo-se como cuidadores familiares. Objetivos: caraterizar os motivos que conduzem à assunção do papel de cuidador familiar; determinar a satisfação com o exercício do papel bem como as principais fontes de satisfação; determinar a sua perceção de autoeficácia para tomar conta e o envolvimento nos cuidados. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…This concept is based on role enrichment, which proposes that multiple roles bring rewards, such as income, social networking opportunities, and successful experience. Other research in the area (Correia et al, 2018;Cunha, 2011;Noonan & Tennstedt, 1997) also found that, despite the difficulties inherent in role performance, such as physical capacity and emotional management, caregivers obtain satisfaction with life, greater positive affect and well-being in the care of the dependent person, even when the demands are more challenging among the elderly with Alzheimer's disease (Lopes & Cachioni, 2013). In addition, care provided the development of time, task and resource management skills (Barham & Vanalli, 2012;Crespo et al, 2019;Matias & Fontaine, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This concept is based on role enrichment, which proposes that multiple roles bring rewards, such as income, social networking opportunities, and successful experience. Other research in the area (Correia et al, 2018;Cunha, 2011;Noonan & Tennstedt, 1997) also found that, despite the difficulties inherent in role performance, such as physical capacity and emotional management, caregivers obtain satisfaction with life, greater positive affect and well-being in the care of the dependent person, even when the demands are more challenging among the elderly with Alzheimer's disease (Lopes & Cachioni, 2013). In addition, care provided the development of time, task and resource management skills (Barham & Vanalli, 2012;Crespo et al, 2019;Matias & Fontaine, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Esse conceito é baseado no enriquecimento de funções, o qual propõe que funções múltiplas trazem recompensas, como renda, oportunidades de relacionamento social e experiência de sucesso. Outras pesquisas na área (Correia et al, 2018;Cunha, 2011;Noonan & Tennstedt, 1997) também constataram que, apesar das dificuldades inerentes ao desempenho do papel, como capacidade física e gestão das emoções, os cuidadores obtêm satisfação com a vida, maior afeto positivo e bem-estar nos cuidados da pessoa dependente, mesmo quando as demandas são mais exigentes, como entre os idosos com doença de Alzheimer (Lopes & Cachioni, 2013). Além disso, os cuidados proporcionavam o desenvolvimento de habilidades de gerenciamento de tempo, tarefas e recursos (Barham & Vanalli, 2012;Crespo et al, 2019;Matias & Fontaine, 2012).…”
Section: Discussionunclassified